Analysis of Employee Online Service Needs (Descriptive Study in the Lebak District Education Office) - Hidayatullah; Suherman; Aan Hendrayana (South Sulawesi Education Development (SSED), 2024)
This study aims to analyze the need for online employee services at the Lebak Regency Education Office. Currently, personnel services are still paper-based, resulting in inefficiencies in terms of time and cost. This research employs a descriptive method, with data collection carried out through questionnaires distributed to 1,654 employees using Google Forms. The data was analyzed qualitatively using the Miles and Huberman model. The results indicate that the majority of employees, including both educators and educational staff, support the implementation of online employee services, as they are considered more efficient and effective compared to paper-based systems. A total of 61.4% of respondents agreed and 29.5% strongly agreed that online services simplify administrative processes and reduce operational costs. However, challenges remain, particularly regarding uneven information technology skills among employees and geographical barriers. This study highlights the importance of digital transformation in public services to enhance efficiency and accountability, while also driving bureaucratic reform in the education sector.